Causation in perspective: are all causal claims equally warranted? - Weber, Erik; De Vreese, Leen (Philosophica, 2012)
In a paper "Causation in Context" (2007) Peter Menzies has argued that the truth value of causal judgments is perspective-relative (i.e. their truth value does not depend entirely on mind-independent structures). His arguments are confined to causation as difference making (a term he uses to cover probabilistic, counterfactual and regularity views of causation). In this paper we first briefly present Menzies’ arguments. Then we show that perspective-relativity also holds for causation in the sense of process theories. These parts of the paper prepare the ground for the topic we really want to investigate: we want to find out whether this perspective-relativity leads to an epistemic predicament with respect to causal claims. The potential epistemic predicament we consider is that all causal claims would be equally warranted.